(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2025)
Ground water are main sources of drinking in Wadi Fira, Chad, this state was chosen as study area due to the lack of research evidences in the past. The study aimed to evaluate some physicochemical properties of ground water comparing with world health organization and local standards in Chad. Water samples were collected from (35 wells) in different locations of the city by using GPS to locate the coordinates of wells in November 2024, and packaged in polyethylene bottles and carefully stored. The samples were analysed using an Atomic Absorption Spectrometer (AAS), pH Meter, Conductivity meter (E.C), Turbidity meter, EDTA titrimetric methods, flame photometric, the analyses were carried out in national water laboratory, Ndjamena. the following parameters such as: pH meter, Electrical Conductivity (E.C), Turbidity, Total Hardness (T.H), Total Dissolved Salt (T.D.S), and total alkalinity (TA), cations, ( Na+, Mg 2+, K+, Ca 2+, Fe2+) and some anions such as: ( F-, CI-, SO42-, NO3-). The results showed that, pH were in the range (6.65-8.20), Electrical Conductivity (E.C), (111.8-1977) µs/cm, except, sample (S10-S23) were found in the range (4440.0-4650) respectively, these values were higher than guidelines of WHO and OMS, turbidity ranges between (0.0-35) NTU except, samples (S6,S7,S21) were found in the range (117.0,50.2,12.8) respectively, within permissible values WHO, but higher than approved level OMS (≤ 5),Total Dissolved Salt (T.D.S) range between (56.6-924.8) mg/L except samples (S19,S26) showed (2227.6-2334.6) respectively, which their recorded values were higher than permitted standard, Na+ (1.4-44.0) mg/L, K+, (1.5-8.9) mg/L except, samples (S16, S26) were found (24.3,64.0) higher than the acceptable limit to OMS and WHO, Mg2+ (4.9-38.9) mg/L Concentrations of Magnesium all the samples were within allowed range, Ca2+ (32.0-200) mg/L Concentrations of Calcium were within approved range with the exception (S10,S18,S19,S26 and S32) were found (240,216,376.0,394.0 and 280.0) consecutively, were higher than suggested range in OMS ( ≤ 200 ), Fe2+ (0.0-02) mg /L, NH4+ (0.0-1.2) mg/L, except samples (S6,S21) were found (3.5,2.6) were higher than suggested range in OMS (≤ 1,5), F-(0.0-1.4) mg/L, Cl- (3.0-1800) mg/L all samples was within allowed range, NO3- (0.0-0.344) mg/L except S19 was found 53.4 was higher than permissible value, SO42- (1.0-160.0) mg/L, most samples had pH and total solubility values of salt within permissible limits according to drinking water quality guidelines of WHO and OMS, with exception some samples content (Electrical conductivity, Total dissolve solid, potassium ion concentration, ammonium concertation and nitrate) were higher in than the allowed limit of Chad Standards and World Health Organization. From the comparison we conclude that most of the sources are with safe for drinking, some need treatments. Further studies should be conducted to determine the concentrations of heavy metals contamination in the study areas. The study recommends that, officials should obligate the organizations and corodies conducing comprehensive investigation before digging wells.